2013
DOI: 10.1063/1.4812165
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale modelling of granular avalanches

Abstract: A study of the rheology of planar granular flow of dumbbells using discrete element method simulations Physics of Fluids 28, 103301 (2016) Abstract. Avalanches, debris flows, and landslides are geophysical hazards, which involve rapid mass movement of granular solids, water and air as a single-phase system. The dynamics of a granular flow involve at least three distinct scales: the micro-scale, meso-scale, and the macro-scale. This study aims to understand the ability of continuum models to capture the micro-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…It will be shown later that the convex shape is related to a process called avalanching which is mesh-dependent. Increasing the number of material points in a coarse mesh did not significantly improve the results as was also observed by Kumar [16]. However, a refinement of the mesh, which indirectly initialised more material points, improved the results significantly.…”
Section: Definition Of Geometry and Meshsupporting
confidence: 52%
See 3 more Smart Citations
“…It will be shown later that the convex shape is related to a process called avalanching which is mesh-dependent. Increasing the number of material points in a coarse mesh did not significantly improve the results as was also observed by Kumar [16]. However, a refinement of the mesh, which indirectly initialised more material points, improved the results significantly.…”
Section: Definition Of Geometry and Meshsupporting
confidence: 52%
“…Hence, the run-out distances were largely overestimated and numerical damping had to be applied in order to match the experimental results. Kumar [16] carried out simulations of the column collapse with both MPM and DEM and showed that MPM with a Mohr-Coulomb model suffered from insufficient dissipation of energy in comparison with DEM. It was attributed to the absence of inter-particle collisions which dissipates some energy.…”
Section: Simulating the Column Collapsementioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were presented by Kumar in the simulation of slope subjecting horizontal excitation. 44…”
Section: Influence Of Mesh Sizementioning
confidence: 99%